Siddha Ayurvedic Surgical Management of Vathasthambam (Sciatica)– A Case Study - Sritharan, G.; Anpuchelvi, S.; Ganesan, S. (Global Academic Research Institute Colombo, Sri Lanka, 2024)
Sciatica is a more common cause of pain & disability. Sciatica is common type of pain affecting the sciatic nerve. Sciatica is defined as the pain in the distribution of sciatic nerve or its component nerve roots. 45 year old male patient comes in Herbal Health Care Clinic Jaffna, Sri Lanka with complaints in low (lumbar region) on left side which is radiating towards the thigh, calf region and down to the foot, difficulty and pain while walking and sitting, stiffness in lumbar region and numbness in the left leg since 2 months. Patient underwent for several allopathy and Ayurvedic treatments but got only temporarily relief. Then patient came to the this clinic for Siddha Ayurvedic Surgical department for further Ayurvedic Surgical treatment. He consulted Siddha Ayurveda physician and taken Siddha Ayurveda treatment for the same. Herbal formulation and Parasurgical treatment are better alternative natural remedies and it is safe, simple effective, self- of treatment. It is concluded that the combination of the Siddha medical herbal treatment & Parasurgical procedure is effective in the management
Keywords: Agnikarma; Ayurvedic; Pancha dhatu sciatica